Compact polarimetry for automotive applications. Issue 2 (2nd January 2019) - Erhart, Christian; Lutz, Steffen; Mutschler, Marc A.; Scharf, Philipp A.; Walter, Thomas; Mantz, Hubert; Weigel, Robert
Abstract: Though compact polarimetric approaches have been developed and applied in space and geo researching systems they have not been taken into consideration in automotive applications, yet. A sensor system has been designed to conduct polarimetric measurements in the 77 GHz frequency band, which is permitted for automotive usage. This system is able to transceive linearly as well as circularly polarized electromagnetic continuous waves. Depending on the case of application, the frequency output can be set statically or modulated over time within adjustable parameters. Hence, a variety of compact polarimetric modes can be performed and compared with full polarimetric approaches. Two compact polarimetric modes, dual-circular polarimetric mode, and circular-transmit-linear-receive, will be introduced and applied in this contribution. Their operability in this frequency range will be investigated after the microstrip antennas as well as the beam focusing dielectrical lense are characterized. Finally, results of a realistical measurement set-up will confirm the practicability of compact polarimetric approaches for double bounce recognition.